HUBUNGAN KONDISI LINGKUNGAN FISIK, BIOLOGI DAN PRAKTIK PEMBERANTASAN SARANG NYAMUK (PSN) DENGAN KEJADIAN DEMAM BERDARAH DENGUE (DBD) DI WILAYAH KERJA PUSKESMAS NGAWI (STUDI KASUS DI WILAYAH KERJA PUSKESMAS NGAWI, KECAMATAN NGAWI, KABUPATEN NGAWI) - Novita Dian Rahmawati; Nurjazuli Nurjazuli; Hanan Lanang Dangiran (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Puskesmas Ngawi was one of 24 Puskesmas in the Ngawi District that in 2015 is the case most many 116 some cases. This study aimed to analyze the relationship physical environment, biology, and PSN practices with dengue hemorrhagic fever at Puskesmas Ngawi work area. The design for this research use case control. The population are cases population and control population There are 102 sample which consists of 51 cases and 51 control .The research using chi-square show variable are associated with DHF are potential breeding place in the house (p-value=0,016; OR=3,429), resting place in the house (p-value=0,001; OR = 6,667), resting place outdoors (p-value=0,001; or = 5,405 ), practices draining TPA (p-value=0,001; OR = 11,985), practices close TPA (p-value=0,001; or = 8,727), practices recycling thrift (p-value=0,001; OR=4,785 ), avoid contact practices with Aedes aegypti (p-value=0,005; OR= 3,217), while variables unconnected are the existence of potential breeding place outdoors (p-value=0.338; OR=1,869), fish eaters existence larva (p-value=0,4; OR =0,480) and the existence of plant mosquitoes’s adverse (p-value=1 =; OR=1). The conclusion of research there is a relationship between the existence of breeding place potential in the house, the existence of resting place in the house, the existence of the resting place outside of the house, closing the landfill practices, draining the landfill practices, rescycling practices second-hand goods, practices avoid contact Aedes aegypti with of DHF in the Puskesmas Ngawi work area. Therefore, need to intensified campaign PSN 3M plus with public to prevent occurrence of DHF.